Examining Police Officers’ Perceptions of Automated License Plate Readers Before Technology Expansion - Shjarback, John A. (Criminal justice policy review, 2024)
Automated license plate readers (ALPRs) are one of the most recent technological advancements that have rapidly diffused across U.S. law enforcement. A majority of the large police agencies utilize APRs, yet little empirical and evaluative research has been conducted on this technology. This study seeks to (a) synthesize what is known about ALPRs and (b) examine police officers’ perceptions of ALPRs before a major expansion of the technology in a single agency in the Mid-Atlantic region of the United States. Using an officer survey of 110 respondents, results found that those with prior experience using the technology, younger and more inexperienced officers, and those with stronger guardian orientations possessed more positive perceptions of the ALPR expansion. Prior experience using ALPRs also served as a protective factor by being associated with lower levels of skepticism toward the technology expansion; those officers with stronger warrior orientations had higher levels of skepticism. Practical considerations and directions for future research are discussed.